A Wireworm Conoderus scissus Schaeffer (Insecta: Coleoptera: Elateridae) - Dakshina R. Seal (EDIS)
Conoderus scissus is the most abundant wireworm species found in sweet potato fields. Its preference for other crops is followed by peanut, cowpea, and corn. Learn more in this 3-page fact sheet written by Dakshina R. Seal and published by the UF Department of Entomology and Nematology, December 2011. Reviewed December 2014.